2008
DOI: 10.1590/s0103-64402008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave disinfection on physical and mechanical properties of acrylic resins

Abstract: This study evaluated the effect of microwave energy on the hardness, impact strength and flexural strength of the Clássico, Onda-Cryl and QC-20 acrylic resins. Aluminum die were embedded in metallic or plastic flasks with type III dental stone, in accordance with the traditional packing technique. A mixing powder/liquid ratio was used according to the manufacturer's instructions. After polymerization in water batch at 74ºC for 9 h, boiling water for 20 min or microwave energy at 900 W for 10 min, the specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 13 publications
5
28
2
3
Order By: Relevance
“…This result is in agreement with the previous study that reported hardness decrease for acrylic resins after microwave irradiation, but no effect was observed on the impact and flexural strength [16]. Moreover, conventional and boiled polymerization cycles promoted similar roughness and surface hardness for QC-20 and Classico resins [24]; however, the hardness levels for both resins were lesser than those seen in the current study.…”
Section: Open Access Http://scidocorg/ijdosphpsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in agreement with the previous study that reported hardness decrease for acrylic resins after microwave irradiation, but no effect was observed on the impact and flexural strength [16]. Moreover, conventional and boiled polymerization cycles promoted similar roughness and surface hardness for QC-20 and Classico resins [24]; however, the hardness levels for both resins were lesser than those seen in the current study.…”
Section: Open Access Http://scidocorg/ijdosphpsupporting
confidence: 92%
“…Although the microwave radiation had been efficient in the sterilization process, possible harms on the mechanical and viscoelastic properties of the acrylic resin still need to be best clarified. Previous studies have shown that the disinfection by microwave energy decreased the hardness of some acrylic resin types, but no effect was observed on the impact and flexural strength [16]. Repeated microwave disinfections decreased the Knoop hardness and showed no effect on the impact strength, while the flexural strength was similar for all evaluated acrylic resins [17]; however,though the roughness after brushing was not significantly affected by microwave disinfection, a increased microwave cycles resulted in greater roughness [18].…”
Section: Introductionmentioning
confidence: 74%
“…17 Each specimen was put in a plastic vial contained a aquadest and soft drinks solution, with each amounted as much as 20 ml, and stored in an incubator at the temperature of 5°C (for the treatment group). 18 All specimens were immersed for 2 days to simulated the average person soft drink daily consumption habits for 20 minutes in 5 months period of time (20 minutesx150 days= 3000 minutes=50 hours=2.08 days). The immersion media was replaced daily.…”
Section: Methodsmentioning
confidence: 99%
“…An effective alternative method that has been currently used is microwave irradiation to fight several diseases and eliminate colonization by Candida albicans 4,[8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical characteristics such as rugosity, hardness, dimensional stability of color and bending properties can be changed after immersion in those solutions 1,11,13 .…”
Section: Introductionmentioning
confidence: 99%